1995
DOI: 10.1007/bf00220873
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the most represented repeated motifs in Arabidopsis thaliana microsatellite loci

Abstract: The major simple sequence repeats present in the Arabidopsis genome were identified by Southern hybridizations with 49 oligonucleotide probes matching all the possible combinations of motifs up to 4 nucleotides long. The method used allowed us to perform all the hybridizations under the same temperature conditions. A good correlation was observed with the data obtained from database analysis, indicating that the method can be useful for identifying the major classes of microsatellite loci in species for which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 32 publications
9
40
1
Order By: Relevance
“…The majority of the microsatellites detected contained GA-repeats, which were variable in length and composition, some having up to 19 perfect repeats. Microsatellites containing GA-repeats are common in many plants (Lagercrantz et al 1993;Terauchi 1994;Wang et al 1994;Depeiges et al 1995), which may also be the case for cassava. The isolation of other types of microsatellites may require the screening of libraries enriched for specific repeats.…”
Section: Resultsmentioning
confidence: 99%
“…The majority of the microsatellites detected contained GA-repeats, which were variable in length and composition, some having up to 19 perfect repeats. Microsatellites containing GA-repeats are common in many plants (Lagercrantz et al 1993;Terauchi 1994;Wang et al 1994;Depeiges et al 1995), which may also be the case for cassava. The isolation of other types of microsatellites may require the screening of libraries enriched for specific repeats.…”
Section: Resultsmentioning
confidence: 99%
“…Dinucleotide microsatellites were reported to occur in a higher frequency than tri-and tetra-nucleotide microsatellites in plants (Depeiges et al 1995, Diwan et al 1997, Plieske and Struss 2001. Furthermore, Smith et al (1997) and Senior et al (1998) reported that the average PIC value for dinucleotide repeats was higher than that for tri-and tetranucleotide repeats.…”
Section: Development Of Microsatellite Markersmentioning
confidence: 99%
“…The discriminatory potential for ISSR markers depends on the variety and frequency of microsatellites, which change with species and the SSR motifs that are targeted. The sequence of repeats and anchored nucleotides were selected in a way to allowed analysis of multiple loci in a single, multiplexed reaction (Depeiges et al 1995). The reproducibility of the fragments generated by ISSR primers exceeds that of primers of arbitrary sequences typically used for RAPD analysis as described previously (Ajibade et al 2000).…”
Section: Genetic Classificationmentioning
confidence: 99%